ENHANCING MULTICULTURAL ISLAMIC EDUCATION-BASED LITERACY IN COMMUNITY ISLAMIC BOARDING SCHOOLS (PESANTREN RAKYAT) - Acetylena, Sita; Cholisna Wardah , Amil; Halim , Abdul; Badrussalam , Badrussalam; Maskuri, Maskuri (Universitas Islam Malang, 2023)
This study aims to explore the effectiveness of implementing a multicultural Islamic educationapproach in enhancing literacy among teachers in community Islamic boarding schools. With thegrowing diversity in society, particularly within educational settings, it becomes imperative tofoster an inclusive educational environment that respects and integrates various culturalperspectives. The study adopts a qualitative research design and PAR (Participation ActionReasearch), employing interviews, observations, and document analysis to gather data. Theprinciple of PRA is action by, with, and for the people. Participants include teachers, andadministrators from selected community Islamic boarding schools. Findings indicate thatintegrating multicultural Islamic education principles promotes literacy development by fosteringa deeper understanding and appreciation of diverse cultural backgrounds and perspectives.Moreover, it enhances critical thinking skills and promotes social cohesion among students. Thestudy underscores the importance of incorporating multicultural Islamic education approaches ineducational settings to cultivate literate and culturally competent individuals capable of thrivingin diverse societies.